(untitled) - Mises, Ludwig von (Indianapolis, 1981)
This book introduce about liberalism and socialism. The economics of a socialist community. The alleged inevitability of socialism. Socialism as a moral imperative. Destructionism
Keywords: Chủ nghĩa xã hội,Socialism